A Microbiome-Driven Approach to Combating Depression During the COVID-19 Pandemic - Ghannoum, Mahmoud A.; Ford, MaryKate; Bonomo, Robert A.; Gamal, Ahmed; McCormick, Thomas S. (Frontiers in Nutrition, 2021)
The significant stressors brought about and exacerbated by COVID-19 are associated with startling surges in mental health illnesses, specifically those related to depressive disorders. Given the huge impact of depression on society, and an incomplete understanding of impactful therapeutics, we have examined the current literature surrounding the microbiome and gut-brain axis to advance a potential complementary approach to address depression and depressive disorders that have increased during the COVID-19 pandemic. While we understand that the impact of the human gut microbiome on emotional health is a newly emerging field and more research needs to be conducted, the current evidence is extremely promising and suggests at least part of the answer to understanding depression in more depth may lie within the microbiome. As a result of these findings, we propose that a microbiome-based holistic approach, which involves carefully annotating the microbiome and potential modification through diet, probiotics, and lifestyle changes, may address depression. This paper's primary purpose is to shed light on the link between the gut microbiome and depression, including the gut-brain axis and propose a holistic approach to microbiome modification, with the ultimate goal of assisting individuals to manage their battle with depression through diet, probiotics, and lifestyle changes, in addition to offering a semblance of hope during these challenging times.